2013
DOI: 10.1590/s1413-81232013001200013
|View full text |Cite
|
Sign up to set email alerts
|

Condutas negativas à saúde em estudantes universitários brasileiros

Abstract: Condutas negativas à saúde em estudantes universitários brasileiros Risk behaviors to health in Brazilian college students

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
32
0
32

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 16 publications
1
32
0
32
Order By: Relevance
“…In general, it is reported that men drink more than women. 23,27 Considering Binge drinking among female university students Mendonça AKRH, Jesus CVF, Figueiredo MBGA, Valido DP, Nunes MAP, Lima SO the negative affect of the misuse of alcoholic beverages on the vulnerability of women, there is an urgent need for interventions and educational measures that address the inappropriate use of alcohol and its deleterious effects in the university context. Moreover, support groups should be formed for students who are using alcohol in a problematic way.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, it is reported that men drink more than women. 23,27 Considering Binge drinking among female university students Mendonça AKRH, Jesus CVF, Figueiredo MBGA, Valido DP, Nunes MAP, Lima SO the negative affect of the misuse of alcoholic beverages on the vulnerability of women, there is an urgent need for interventions and educational measures that address the inappropriate use of alcohol and its deleterious effects in the university context. Moreover, support groups should be formed for students who are using alcohol in a problematic way.…”
Section: Discussionmentioning
confidence: 99%
“…27,32 Among the female students who reported smoking, binge drinking was a constant. Health promotion campaigns, such as public anti-smoking policies, increase quality of life and reduce health risks related to its determinants and conditions.…”
Section: Discussionmentioning
confidence: 99%
“…These results show that the observed risk factors indicate similar favorable conditions for the rise of NCDs in the group investigated by this study, requiring an intervention by the municipality to modify these factors which are preventable. A comparison with the study of Sousa et al 42 on students from the State University of Santa Cruz, BA, shows similar scenarios between the populations, which is characterized by inadequate consumption of fruits and vegetables, lower levels of physical activity at leisure and excessive alcohol consumption and smoking.…”
mentioning
confidence: 54%
“…According to data of the Household Budget Survey (POF 2002(POF -2003, there was a 400% increase in the soft drink participation in household food purchases by Brazilians, which is higher in lower income classes 40 . Brazilian studies have shown that this scenario is repeated with college students 41,42 . Information collected by the World Health Survey 43 shows that the frequency of daily consumption of fruits and vegetables among the Brazilian adult population is around 41% and 30%, respectively, with a higher consumption found in the higher socioeconomic groups.…”
mentioning
confidence: 99%
“…Changes in the eating patterns, decrease in the physical and leisure activities, increase or onset of alcohol, drug and/or tobacco use were found to be health risk factors to this population 26,27 .…”
Section: Discussionmentioning
confidence: 88%